1/(h+1) = (2h+3)/(h-1)
multiply by (h+1)(h-1) both sides:
h-1 = (2h+3)(h+1)
h-1 = 2h^2 +2h +3h + 3
2007-01-10 08:50:49
·
answer #1
·
answered by tablecloth 1
·
1⤊
0⤋
1/(h+1) = (2h+3)/(h-1)
multiply both sides by (h-1)(h+1) to remove denominators:
(If we get any solution like h=1 or h=-1, then they would be discarded, because denominators don't allow them)
(h-1) = (2h+3)(h+1)
Then solve the binomium:
(h-1) = (2h+3)(h+1)
h-1 = 2*h^2 +5*h +3
Reduce it:
2*h^2 + 4*h+ 4 =0
Simplify dividing by 2:
h^2 + 2*h+ 2 =0
Now we solve it as a quadratic equation- using the formula:
h= -1 -i
h=-1 + i
(roots are complex).
2007-01-10 16:55:00
·
answer #2
·
answered by Anonymous
·
2⤊
0⤋
Multiply both sides by (h+1)(h-1) to get rid of the fractions:
h-1=(2h+3)(h+1)
h-1=2h^2+5h+3
Subtract h and add 1 from both sides:
2h^2+4h+4=0
Factor out a 2:
h^2+2h+2=0
Use the quadratic formula:
h=-b屉b^2-4ac/2a
a=1,b=2,c=2
h=-2屉(2)^2-4(1*2)/2(1)
h=(-2屉4-8)/2
h=-2屉-4/2
h=-2屉4i/2
h=-2±2i/2
h=-1±i
2007-01-10 17:54:57
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
You have different denominators. Multiply both sides by (h-1) and by (h+1) and you'll get rid of them:
(h-1) = (2h+3)(h+1)
Now expand out:
(h-1) = (2h^2 + 5h + 3)
0 = 2h^2 + 4h +4
h^2 + 2h + 2 = 0
Now you need solve using the quadratic formula:
a = 1
b = 2
c = 2
h = [ -2 ± sqrt( 2² - 4(1)(2) ) ] / 2
h = -1 ± sqrt(-4)/2
h = -1 ± i
2007-01-10 16:53:52
·
answer #4
·
answered by Puzzling 7
·
3⤊
0⤋
Multiply left side by (h -1)/(h -1) and multiply right side by (h+1)/(h+1( to get common denominator. Leave factored.
Set equation equal to zero.
Factor numerator and eliminate any common factors between numerator and denominator.
Hope that helps!
2007-01-10 16:53:47
·
answer #5
·
answered by teachbio 5
·
2⤊
0⤋
http://www.webmath.com/nsolve.html
this site allows for you to type in the problem and seconds later recieve the answer to your algebra problem
2007-01-10 16:58:10
·
answer #6
·
answered by HDsnowlover 2
·
1⤊
0⤋